Re-creating primordial time : foundation rituals and mythology in the postclassic Maya codices - Vail, Gabrielle; Hernández, Christine L. (University Press of Colorado, 2013)
This book offers a new perspective on the Maya codices, documenting the extensive use of creation mythology and foundational rituals in the hieroglyphic texts and iconography of these important manuscripts. Focusing on both pre-Columbian codices and early colonial creation accounts, the authors show that in spite of significant cultural change during the Postclassic and Colonial periods, the mythological traditions reveal significant continuity, beginning as far back as the Classic period. Remarkable similarities exist within the Maya tradition, even as new mythologies were introduced through contact with the Gulf Coast region and highland central Mexico. The authors analyze the extant Maya codices within the context of later literary sources such as the Books of Chilam Balam, the Popol Vuh, and the Codice Chimalpopoca to present numerous examples highlighting the relationship among creation mythology, rituals, and lore. Compiling and comparing Maya creation mythology with that of the Borgia codices from highland central Mexico, this book is a significant contribution to the field of Mesoamerican studies and will be of interest to scholars of archaeology, linguistics, epigraphy, and comparative religions alike. --